Constraints on the Upper Mantle Structure Beneath the Pacific From 3‐D Anisotropic Waveform Modeling. Issue 4 (27th April 2021) - Kendall, E.; Ferreira, A. M. G.; Chang, S.‐J.; Witek, M.; Peter, D.
Abstract: Seismic radial anisotropy is a crucial tool to help constrain flow in the Earth's mantle. However, Earth structure beneath the oceans imaged by current 3‐D radially anisotropic mantle models shows large discrepancies. Here, we provide constraints on the radially anisotropic upper mantle structure beneath the Pacific by waveform modeling and subsequent inversion. Specifically, we objectively evaluate three 3‐D tomography mantle models which exhibit varying distributions of radial anisotropy through comparisons of independent real data sets with synthetic seismograms computed with the spectral‐element method. The data require an asymmetry at the East Pacific Rise (EPR) with stronger positive radial anisotropy ξ = V S H 2 V S V 2 = 1.13–1.16 at ∼100 km depth to the west of the EPR than to the east ( ξ = 1.11–1.13). This suggests that the anisotropy in this region is due to the lattice‐preferred orientation of anisotropic mantle minerals produced by shear‐driven asthenospheric flow beneath the South Pacific Superswell. Our new radial anisotropy constraints in the Pacific show three distinct positive linear anomalies at ∼100 km depth. These anomalies are possibly related to mantle entrainment at the Nazca‐South America subduction zone, flow at the EPR and from the South Pacific Superswell and shape‐preferred orientation (SPO) of melt beneath Hawaii. Radial anisotropy reduces with lithospheric age to ξ < 1.05 in the west at ∼100 km depth, which possibly reflects a deviation from horizontal flow as the mantle is entrained with subducting slabs, a change in temperature or water content that could alter the anisotropic olivine fabric or the SPO of melt. Key Points: We assess radially anisotropic features in 3‐D tomographic models with full waveform modeling along with independent data The data require an asymmetry in radial anisotropy at the East Pacific Rise possibly linked to flow beneath the South Pacific Superswell Our new radial anisotropy constraints show a lateral age‐dependence, which possibly reflects a change in flow from the horizontal direction